An application of artificial neural network to maintenance management (2006)
This study shows the usefulness of Artificial Neural Network (ANN) in maintenance planning and management. An ANN model based on the multi-layer perception having three hidden layers and four processing elements per layer was built to predict the expected downtime resulting from a breakdown or a maintenance activity. The model achieved an accuracy of over 70% in predicting the expected downtime.